Kalimat Larangan dalam Bahasa Jawa - Herawati Herawati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2015)
Prohibition Sentence is part of the imperative sentence or order sentence.Prohibition speech meaning is expressed in form of negative imperative wrote aja 'do not'. The theory in this research is structural theory.The method of research is distributional method with paraphrasing technique or shape changing or grammatical synonymy, and substitutions. Result shows that prohibition sentence includes (a) the internal structure of prohibition sentence that distinguishes it from other sentence form, (b) the type of constituent that supports realization of prohibition sentence, and (c) argument status on the sfiller constituent of subject function which differentiates one subtype of prohibition sentence with other prohibition sentence subtypes.